Sexual Dysfunction Risk and Associated Factors in Young Peruvian University Women - Escajadillo-Vargas N. (2011)
This study was an MD thesis for N.E.V at the Faculty of Medicine of Universidad Nacional de Piura, Piura, Peru. Authors would like to thank the Consejo Nacional de Ciencia y Tecnología de Perú (CONCYTEC) for supporting data presentation as Oral Communication at the 14th World Congress of Gynecological Endocrinology, March 3, 2010, Florence, Italy.